All Men Free and Brethren. Essays on the History of African American Freemasonry, editado por Peter Hinks y Stephen Kantrowitz - Révauger, Cécile (REHMLAC+, Revista de Estudios Históricos de la Masonería Latinoamericana y Caribeña plus, 2015)
All Men Free and Brethren. Essays on the History of African American Freemasonry. Edited by Peter P. Hinks and Stephen Kantrowitz. Foreword by Leslie A. Lewis. Ithaca, US and London: Cornell University Press, 2013. 262 pages. ISBN-10: 0-8014-5030-6; ISBN-13: 978-0-8014-5030-3.